Masa Depan Guru Honorer Terkait dengan Penghapusan Tenaga Honorer Berdasarkan UU Nomor 20 Tahun 2023 - Afrizalni, Irva; Fitri, Hilda Desma; Putri, Silvina Maharani; Hanoselina, Yulia (PT Maju Malaqbi Makkarana, 2024)
1.237 / 5.000 Hasil terjemahan Hasil terjemahan This study aims to analyze the impact of the elimination of honorary workers on the future of honorary teachers in Indonesia. The elimination of Honorary Workers in Law Number 20 of 2023 has drawn pros and cons from the community. This is because the contribution of Honorary Workers is one of the important supporting elements in the running of the government system. The method used is qualitative descriptive. The technical data analysis in this study uses qualitative data analysis. The elimination of honorary workers in Law Number 20 of 2023 concerning the State Civil Apparatus (ASN) has also put the future of Honorary Teachers at stake. The government has offered several solutions, including the selection of Government Employees with Work Agreements (PPPK) as one of the solutions for honorary workers. This selection itself poses new challenges, such as tight competition and requirements that must be met by honorary teachers in order to pass the selection. Thus, synergy is needed between the government, educational institutions and teachers themselves for a better future, especially for educators in Indonesia.